Ensino da modelagem matemática utilizando o Método de Aprendizagem baseada em Problemas (PBL) - Menezes, Graciete Neves de (Brasil, 2024)
The present work will focus on the study of Mathematical Modeling applied in the distribution/sale of cooking gas to high school students. This work aims to show, through mathematical modeling, possibilities to present the set of knowledge and learning in everyday life using mathematics as a basis in the distribution of Liquefied Petroleum Gas. In addition, the theme proposed by the lesson plan was mathematical modeling in the distribution of cooking gas in high school classes in Lábrea - Amazonas and São Francisco - Minas Gerais. Mathematical modeling can be conceptualized as a learning environment in which students are invited to problematize and investigate, through mathematics, situations with reference to reality”. Moreover, the active methodology will be used, which seeks to teach in a different way than usual, where the student participates in the class. In this sense, the methodology based on a problem will be used, where students will do some calculations to reach a plausible result. As a result, we obtained positive responses, where most of the class where the active methodology was applied, managed to satisfactorily understand the past content. Finally, this work will be practical and theoretical, that is, in addition to a literature review, there will be a practical part, which will involve a classroom dynamic, seeking to pass knowledge on the subject to high school students.